Travel-associated outbreak of COVID-19 in a departmental store, Wenzhou, China - Zhou, Yiwei; Xiang, Fanglv; Ni, Chaorong; Zhang, Xiaoming; Xie, Haibin; Zhu, Haishen; Zhou, Zumu (The Journal of Infection in Developing Countries, 2022)
Introduction: A local outbreak of coronavirus disease 2019 (COVID-19) has rapidly evolved into a global pandemic and the number of cases and deaths has increased exponentially. In this study, we report a COVID-19 outbreak that occurred in a departmental store, between January and February 2020, in Wenzhou, China and investigated the reasons for the outbreak. Methodology: An outbreak investigation was initiated after the index case was diagnosed as COVID-19. Cases (confirmed and suspected) and close contacts were defined. Their pharyngeal swabs were collected and examined with real-time polymerase chain reaction (RT-PCR) for nucleic acid. All investigations of the confirmed and suspected cases were carried out by epidemiologists and the source of infection was tracked by using big data. Results: Thirty-nine COVID-19 cases and one asymptomatic individual were found in this outbreak, as determined by clinical manifestations, epidemiological investigation, and RT-PCR. Majority of COVID-19 cases occurred in a departmental store, three of whom traveled to participate in a meeting held in H city. After disease outbreak in the departmental store, intra-family transmission of COVID-19 occurred in five families. Two clusters of the COVID-19 outbreak were identified. One cluster was attributed to the family party, while another was attributed to a hotel party, which was responsible for transmission across three generations, infecting five family members. Conclusions: This was travel associated COVID-19 outbreak in a departmental store in Wenzhou, China. High infectivity of COVID-19 was observed. A departmental store, especially without recirculation of the air, was a high-risk site for the transmission of COVID-19. The use of big data and related information was very useful in epidemiological investigation of cases and contacts.